2018
DOI: 10.3390/polym10101059
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Actuation of Poly(dimethylsiloxane) Filled with Graphene Oxide Grafted with Poly(2-(trimethylsilyloxy)ethyl Methacrylate)

Abstract: This study serves to combine two approaches into one single step, to achieve a significant improvement of the light-induced actuation capabilities. Graphene oxide (GO) is an inert material, from the electrical and thermal conductivity point of view, and is incompatible with the usually-used poly(dimethylsiloxane) (PDMS) matrix. During surface-modification by surface-initiated atom transfer radical polymerization, the GO was transformed into a conducting and compatible material with the PDMS showing enormous li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…The second region is from 185 °C to 260 °C and corresponds to oxygen-containing groups. For the GO-PBMA hybrid particles, there is significantly lower adsorbed water due to the substantial polymer coating and region corresponding to oxygen containing groups is shifted to lower temperatures, which is a common phenomenon already published elsewhere [19]. The presence of PBMA coating is visible in the region from 250 °C to 350 °C when the decomposition occurs.…”
Section: Si-atrp Grafting Of Go With Pbma Shell Layersupporting
confidence: 68%
See 1 more Smart Citation
“…The second region is from 185 °C to 260 °C and corresponds to oxygen-containing groups. For the GO-PBMA hybrid particles, there is significantly lower adsorbed water due to the substantial polymer coating and region corresponding to oxygen containing groups is shifted to lower temperatures, which is a common phenomenon already published elsewhere [19]. The presence of PBMA coating is visible in the region from 250 °C to 350 °C when the decomposition occurs.…”
Section: Si-atrp Grafting Of Go With Pbma Shell Layersupporting
confidence: 68%
“…The filler absorbs the light of certain wavelength while the matrix exhibits appropriate elasticity. The majority of the fillers are based on carbon (carbon nanotubes [15,16] (CNTs) or graphene particles [17] and more specifically based on graphene oxide [18,19] (GO)). There are also some other substances with photo-active capability such as azobenzene-based molecules [20,21] that are utilized as well.…”
Section: Introductionmentioning
confidence: 99%
“…To show that the hybrid material acts as a photomechanical actuator, 68 the typical change in the length of the sample (ΔL) was investigated using a 627 nm wavelength diode as a light source, similar to the process employed in previous works based on composites with graphene oxide 69−71 or CNTs 35,36 (Figure 12). It should be mentioned that the neat PHEMA-g-PCL copolymer shows a ΔL of 10 μm (Figure 13a), which is a typical value for neat elastic matrices used in photo-mechanical actuation applications (7 μm for neat polydimethylsiloxane (PDMS) 69 or 12 μm for neat Vista- maxx 35 ). The performance of the MWCNTs-PHEMA-g-PCL sample under an intensity of light of 6 mW cm −2 showed a length change of nearly 50 μm in a 10 s light-on regime and a fully reversible process to the starting length after a 25 s lightoff regime (Figure 13b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The actuation response has been enhanced by the addition of azo-moieties, that are however highly toxic, into polymer structures [19,20]. Compared to previously mentioned matrix materials, poly(dimethyl siloxane) is easy to process, is nontoxic and provides the ability for sufficient photo-actuation [14,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the studies of poly(dimethyl silioxane) (PDMS) filled with graphene oxide polymer hybrids (GO-g-polymer) photo-actuators also revealed that through surfaced modification we were able to improve the affinity GO-g-polymer particles to a PDMS matrix. SI-ATRP enables one to finely tune the properties of the chemical cross-linking network in terms of decreasing the activation energy of glass transition (systems possess enhanced flexibility of the PDMS network) that finally improves the ability for photo-actuation [21,22,27].…”
Section: Introductionmentioning
confidence: 99%